PERLINDUNGAN HUKUM TERHADAP ANAK ANGKAT DALAM MEMPEROLEH KEJELASAN STATUS HUKUM MELALUI PENCATATAN PENGANGKATAN ANAK (SUATU TINJAUAN DARI PERSPEKTIF HAK ASASI MANUSIA) - Jenny K Matuankotta (SASI, 2011)
adoptions done by a number of reasons, among others, to continue the descent, to inherit property, and to provide security of life and good future for these children. In the protection of the rights of children, especially for adopted children, then the government out of Act No. 23 of 2002 on Child Protection, Law No. 23 year 2006 about Population Administration and through the implementation of the provisions of the Indonesian Government Regulation No. 54 of 2007 on the Implementation of Child Appointment . Also make policy through a strategic plan in which the programs include Children's Recording of Appointment. Government's commitment to provide clarity to the legal status of foster children through adoption records have been be realized in the issuance of state registration of adoption deed quoted as proof of legality for a foster child